Is Seronegative Rheumatoid Arthritis Far From Being a Benign Subtype of Rheumatoid Arthritis? A Retrospective Comparative Study of Seronegative Rheumatoid Arthritis and Seropositive Rheumatoid Arthritis - Mısırcı, Salim; Büyükuysal, Mustafa Çağatay (The European Research Journal, 2026)
Objectives: Our study aimed to compare patients with seronegative rheumatoid arthritis (SNRA) and seropositive rheumatoid arthritis (SPRA) to determine whether they represent favourable and unfavourable subtypes of the same disease, or whether SNRA patients follow an aggressive course similar to SPRA patients. Methods: Patients diagnosed with rheumatoid arthritis (RA) according to the 2010 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria (n=334) were evaluated retrospectively. Patients were classified into SNRA (n=108) and SPRA (n=226) groups based on their seropositivity status. The SNRA and SPRA groups were compared regarding clinical, laboratory, imaging, and medical treatment characteristics. Results: Gender, age at diagnosis, comorbidities, acute phase reactants, medical therapies (excluding leflunomide), anaemia, cancer, and mortality did not differ significantly between the two groups (P>0.05). There was also no significant difference between the groups in the total number of joints where erosion was detected (SNRA: n=9 (8.3%), SPRA: n=25 (11.1%), P=0.563). Interstitial lung disease (ILD) was the most common extra-articular involvement and was detected only in the SPRA group (n=9 (4.0%), P=0.034). Conclusions: It should be noted that SNRA patients, like SPRA patients, may experience an aggressive disease course and develop erosive joint damage. Seropositivity is important regarding ILD, and necessary follow-up and treatment plans should be implemented without delay for both SNRA and SPRA patients.